OPTIMALISASI APLIKASI KOMUNIKASI DIGITAL UNTUK PRODUK PERTANIAN DI KELOMPOK TANI BOKAPE, TAKALAR - Mukhlishah, Nurul; Mahi, Faizah; Hasan, Hasnah; Herawaty, Herawaty; Asjulia, Asjulia (Jurnal Pengabdian Masyarakat Berkarya, 2025)
This Community Service (PKM) activity aims to improve digital literacy and facilitate the use of communication applications (such as WhatsApp and Facebook) to support group coordination and agricultural product marketing. The method used was a participatory action learning approach through three stages: an initial survey (pre-test), interactive training and simulation, and a final evaluation (post-test). Respondents were 45 people from active farmer groups in the area. The results of the activity showed an increase in average digital literacy and increased use of digital applications for agriculture. The training also encouraged the formation of farmer group WhatsApp groups and product promotion through social media. The conclusion of this activity is that contextual training and intensive mentoring can encourage digital transformation in agriculture, despite challenges such as limited devices and internet connections. Similar interventions are highly recommended for implementation in other agricultural areas.